COVID-19 and Health Systems Functioning in Sub-Saharan Africa Using the “WHO Building Blocks”: The Challenges and Responses - Amu, Hubert; Dowou, Robert Kokou; Saah, Farrukh Ishaque; Efunwole, John Adebayo; Bain, Luchuo Engelbert; Tarkang, Elvis Enowbeyang (Frontiers in Public Health, 2022)
Sub-Saharan Africa (SSA) has made major progress in improving access to health care over the past three decades. Despite efforts made toward achieving universal health coverage, the health systems of countries in the sub-region are inundated by a myriad of challenges that have become more virulent amid the COVID-19 pandemic. This paper discusses the health systems challenges and responses in SSA amidst the COVID-19 using the World Health Organization's (WHO) building blocks of health systems functioning. Long-lasting abysmal health system financing and insufficient government investment in SSA pose major challenges to the effective health systems functioning amid the COVID-19 pandemic. This situation also makes it difficult for the health system to meet the demands of the COVID-19 pandemic and at the same time, cater for other essential health services. Countries in SSA must prioritize the reformation of their health systems through effective health system policy development and implementation, human resources development, training, service delivery, governance and regulation, and sustainable health financing.